Newton's law learning assessment: an experience with high school students (2022)
The Force Concepts Inventory is a test to determine the level of conceptual knowledge of students about mechanical physics and to evaluate the effectiveness of different teaching strategies on the conceptual component of learning. The test is applied with the purpose of knowing the level of conceptualization of the students of a Physics subject course. The results of the pre-test made it possible to find out the level of conceptualization that the students possessed and provided information for the development of workshops based on real physical situations that required the elaboration of force diagrams. The results of the post-test allowed estimating Hake's learning and showed evidence about the conceptual evolution of the students and information to develop future teaching activities on Newton's laws.